Physical and spectroscopic characteristics of lithium-aluminium-borate glass: Effects of varying Nd2O3 doping contents - Aljewaw, Osama Bagi; Abdul Karim, Muhammad Khalis; Mohamed Kamari, Halimah; Mohd Zaid, Mohd Hafiz; Salim, Ali Aqeel; Abu Mhareb, Mohammad Hasan (Elsevier, 2022)
The influence of different Nd2O3 doping contents on the physical and optical properties of the glasses was evaluated. XRD patterns of the as-quenched samples confirmed their glassy nature. Density, ion concentration and field strength increases with the addition of Nd2O3 content, respectively. The absorption spectrum of the glasses exhibit intense peaks at approximately 580, 744 and 800 nm corresponding to the electronic transitions in Nd3+. With increasing Nd2O3 contents, the refractive indices of the glasses were increased from 2.363 to 2.415. FTIR spectra revealed the presence of BO4 and BO3 structural units in the glasses. Emission spectrum of glasses (at 300 nm excitation) displayed four prominent peaks at 368, 421, 483 and 514 nm due to the electronic transition in Nd3+from 4I9/2 to 4P3/2, 2P11/2, 2G11/2, 2G9/2, 4G11/2, and 4G9/2, respectively. The proposed glass system were highly sensitive to the Nd2O3 contents changes.